Modern Developments in Flood Modelling (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Floods are one of the most common natural hazards that substantially affect human lives and properties globally. Engineering is of key importance to cope with flood risk as it provides integrated solutions associated with hydrological–hydraulic and coastal-advanced techniques for analysing flooding risk, for designing flood infrastructures for direct protection, for providing natural retention measures that enhance environmental and river restoration, for developing flood warning systems, and for presenting integrated construction and non-construction measures in order to adapt to emerging climatic challenges and develop resilience under the modern city environment.This Special Issue highlights the current efforts being made to advance the science and applications in flood engineering and, more specifically, in a wide spectrum of its related geosciences, such as hydrology, hydraulics, sedimentation, and river restoration.